ADRENORECEPTOR SENSITIVITY AND MAGNESIUM THERAPY IN PATIENTS WITH CARDIAC ARRHYTHMIAS AND CONNECTIVE TISSUE DYSPLASIA - G. I. Nechaeva; Yu. V. Moskvina; S. S. Bubnova (Российский кардиологический журнал)
Aim. To assess the adrenergic receptor activity and the effects of Magnerot therapy in patients with cardiac arrhythmias and connective tissue dysplasia (CTD). material and methods. The study included 18–35-year-old patients with cardiac arrhythmias and CTD. In all participants, sympathoadrenal system activity was evaluated via beta-adrenoreceptor sensitivity. In particular, erythrocyte osmotic resistance was measured in the presence of beta-adrenoblockers (diagnostic kit “AGAT Med”, Moscow). Results. Patients with ectopic cardiac arrhythmias and CTD demonstrated increased erythrocyte hemolysis levels in the presence of beta-adrenoblockers, which suggested adrenoreceptor desensitisation in this clinical group. A four-month Magnerot treatment was associated with a significant reduction in desensitisation of erythrocyte beta-adrenoreceptors (p<0,0001). Conclusion. Magnerot therapy improved the adrenoreceptor sensitivity to adrenoblockers.